Identification of a Potent and Selective Cannabinoid CB(1) Receptor Antagonist from Auxarthron reticulatum - Elsebai, Mahmoud Fahmi (American Chemical Society, 2011)
[Image: see text] The fungus Auxarthron reticulatum derived from the marine sponge Ircinia variabilis produced the diketopiperazine alkaloid amauromine (1) and the quinolinone methyl-penicinoline (2). Compound 2 is identical to the reported methyl-marinamide, whose structure is herewith revised. In radioligand binding studies at human cannabinoid CB(1) and CB(2) receptors recombinantly expressed in Chinese hamster ovary (CHO) cells, amauromine (1) was found to exhibit high affinity and selectivity for the CB(1) receptor (K(i) = 178 nM). The compound was shown to be a neutral CB(1) antagonist with a K(b) value of 66.6 nM determined in cAMP assays. Compound 2 exhibited only weak or no effects at CB receptors. To the best of our knowledge, compound 1 is the first fungal natural product that shows affinity for cannabinoid CB(1) receptors. Because of its high antagonistic potency and selectivity, it may have potential for use as a drug and/or serve as a lead structure for drug development.